Clean energy consumption and economic growth in China: a time-varying analysis - Bahramian, Pejman; Saliminezhad, Andisheh; Fethi, Sami (Walter De Gruyter Gmbh, 2023)
Assessing the causal relationships between clean energy consumption and economic growth in China, a central actor in the world's climate future, have received considerable attention among scholars. However, due to the lack of methodological rigour in the causality analysis, available literature failed to provide solid inferences on the links between the variables. Therefore, this study aims to re-examine the variables' dynamic linkages with a more well-established approach from 1965 to 2020. We use a time-varying framework that relaxes the assumption of parameter stability, a remarkable feature that distinguishes our paper from the previous studies. Utilizing the conventional Granger causality test, we fail to detect causation between the variables. However, the evidence of substantial time variation in the causal relationships implies that the standard framework's inference is unreliable. The findings of our time-varying analysis indicate different forms of causality flows in various subperiods. This can be a dependable reason for China to follow its enhanced carbon neutrality target safely. The results of our study also emphasize the significance of considering time-varying causality tests to avoid the risk of misleading inferences.
Keywords: China; clean energy consumption; economic growth; recursive rolling estimation; time-varying Granger causality